Current status, challenges and future directions of drug-eluting balloons. (November 2011) - Barbash, Israel M; Waksman, Ron
For the past 30 years, contemporary coronary and endovascular interventions utilized balloon catheters, bare metal- and drug-eluting stents (DES) to recanalize narrowed vessels. Despite this, the quest for outcome optimization is ongoing for specific lesions and patients. Drug-eluting balloons (DEBs) are among the latest technologies proposed to overcome the limitations of DES, such as stent thrombosis and the dependency on long-term dual antiplatelet therapy. In the large part, DEBs were introduced as a substitute for DES in the treatment of in-stent restenosis and perhaps in certain de novo lesion subsets. DEBs have been tested in several clinical scenarios with encouraging preliminary results. This article will discuss the rationale for developing DEBs, basic concepts and available DEB platforms, along with preclinical studies and clinical experience to support the use of this new technology for endovascular interventions.